Pengaruh Label Halal, Harga dan Merek Terhadap Keputusan Pembelian Melalui Religiusitas Sebagai Variabel Intervening Pada Produk HNI-HPAI di Kecamatan Bengkalis - Afriyadi, Afriyadi; Sosiady, Mulia; Nurnasrina, Nurnasrina (Jurnal Rumpun Ilmu Ekonomi, 2024)
The objective of this thesis is to determine the partial influence of the halal label, price, and brand on purchasing decisions. Additionally, it aims to examine their simultaneous effects on purchasing decisions. Moreover, it seeks to investigate how the halal label, price, and brand influence purchasing decisions through religiosity as an intervening variable. This research adopts a descriptive nature with a quantitative approach and was conducted in Bengkalis District, which has a population of 71,360 people. Then, the sample taken consisted of 100 individuals. Data collection for this research was conducted through a questionnaire/survey. The instrument used in this study was tested using the SEM/PLS method operated through the SMART/PLS program. Based on the research findings, firstly, it is known that simultaneously, the halal label has an influence, but at a moderate/medium structural level. Secondly, price does not have an influence and is at a low structural level. Lastly, the brand has an influence but at a moderate/medium structural level. Secondly, the halal label, price, and brand together or partially exert a significant coefficient influence on purchase decisions. Thirdly, religiosity does not intervene in the influence of the halal label on purchase decisions and holds a low value at the structural level. Furthermore, religiosity intervenes in the influence of price on purchase decisions but also holds a low value at the structural level. Lastly, religiosity does not intervene in the influence of the brand on purchase decisions at a low structural level.